Adolescents’ Experience and Knowledge of, and Attitudes toward, Bees: Implications and Recommendations for Conservation - Silva, Alexandra; Minor, Emily S. (Anthrozoös, 2017)
Invertebrates are generally regarded with apathy, distaste, and fear in Western society. These negative sentiments likely contribute to the disparity in wildlife conservation efforts, which largely favor vertebrate organisms. Bees represent one of the most ecologically and economically important invertebrate groups, yet bee diversity and abundance is declining worldwide, mirroring the general decline of invertebrate biodiversity. Developing and implementing successful conservation efforts requires interdisciplinary research that considers the ecological and social realities of today’s world. To better inform conservation efforts related to bees, we examined adolescents’ experiences and knowledge of, and attitudes toward, bees and investigated how these dimensions related to one another. A total of 794 eighth-grade science students from the suburbs of Chicago, USA completed a 48-item, paper questionnaire. The results indicated that adolescents were only somewhat knowledgeable about bee biology and services, and they confused bees with other flying insects, especially those with black-and-yellow coloration. Adolescents regarded bees with a generally neutral attitude; their knowledge and attitudes were correlated in a positive manner. Various bee-related experiences were linked to adolescents’ knowledge and attitudes and may have influenced bee-related behavior. In particular, students who engaged in gardening and lawn-care activities demonstrated higher levels of knowledge and more positive attitudes. This study provides insight into the relationships between experiences and knowledge of, and attitudes toward, invertebrates and suggests that engaging in certain outdoor activities may promote positive attitudes toward bees among adolescents.
Keywords: attitudes; bees; conservation; education; insects